Determinants of Malaysian undergraduates online repurchase intention / Siti Sarah Liyana Azhar - Azhar, Siti Sarah Liyana (2018)
This study has been done to find is there any relationship between perceived value, perceived ease of use, perceived usefulness, firm’s reputation, privacy, trust, reliability and functionality with online repurchase intention among Malaysian undergraduates. The target population was undergraduates’ students in Malaysia either public or private university which approximately 597,294 students and the sample size was 100. Data collection method that had been done was by distributing questionnaire directly and also spreading Google form link. This study has been done for about five months. The result of this study finds that only trust and privacy that significant and have relationship with the online repurchase intention. Recommended to future researcher to get wider target population and sample size to identify wider range of data and also extend the study on trust and privacy in online repurchasing intention context on social medias which we know that anyone can be seller on social medias.